Ярослав Новаківський: минуле і сьогодення - Ярема, Олександр; Yarema, Alexander (Видавництво Львівської політехніки, 2022)
Сенс людського життя – довести свою професійну досконалість у будівництві власної держави. Не замислюємося на тим, що таке освіта й досконалість. Розпочинати треба зі свого рідного гнізда, населеного пункту, регіону й зі здоровою основою вливатися у державні структури. А що маємо: розграбовані земельні ресурси, надра, історичні пам’ятки, ліси, заповідні території, ріки і озера, а найприкріше – губимо людський професійний ресурс.

The sense of human life is to prove professional excellence in building your state. We do not think about what education and perfection are. We need to start with our native nest, locality, and region and join state structures with a healthy foundation. What we have: looted land and mineral resources, historical monuments, forests, protected areas, rivers and lakes, and the most disappointing thing is that we lose human professional resources. Mykhailo Sadovyak analyzed the life of the Sykhiv residential area, the foundations of which were formed by the architect Yaroslav Novakivsky: "The southern part of Lviv represents the proper development, a lot of Sykhiv residents do not go to the centre, there is no need because they have shopping and entertainment centres, parks, markets, libraries, a cinema in their neighbourhood, that is, a person who lives in Sykhiv, has found a place of work and leisure there, and does not migrate to other areas, does not create problems for others. Proper development of a city is a well-developed strategy of the city with its surrounding areas bordering the city, and there is a divided functional capacity of the territory with the correct location."
Yaroslav Novakivsky: past and present
Keywords: архітектура; правильна забудова міста; урбанізм; стратегія міста; Ярослав Новаківський; architecture; proper development of the city; urbanism; city strategy; Yaroslav Novakivsky; 711.4